Comparison of serum levels of thyroid-stimulating hormone in preeclampsia and non-preeclampsia pregnant women referring to Karaj Kamali Hospital in 2018 - Maryam hashemnegad (Revista Latinoamericana de Hipertensión, 2019)
Introduction: As there is no reliable criterion for early diagnosis of preeclampsia up to present date, this study was conducted to compare the serum levels of thyroid-stimulating hormone in preeclampsia and non-preeclampsia pregnant women and the use of thyroid-stimulating hormone (TSH) as a predictive factor in preeclampsia. Method: In this case-control study, 45 non-preeclampsia pregnant women and 45 preeclampsia pregnant women in the third trimester of pregnancy referred to Kamali Hospital of Karaj were examined. A skilled person took 10 cc of venous blood of the subjects and the mean serum TSH levels of both groups were compared by using SPSS, version 22, software. Results: The mean serum TSH level was 2.55 ± 1.13 and 3.08 ± 1.23, respectively, in non-preeclampsia pregnant women and preeclampsia pregnant women, the relationship was statistically significant (P =0.013). Besides, the prevalence of preterm delivery in preeclampsia pregnant women was higher than that in non-preeclampsia pregnant women (P = .000). The mean weight of neonates in preeclampsia pregnant women was lower than that in non- preeclampsia pregnant women (P = .000). Conclusion: This study revealed that measuring serum TSH levels in the third trimester of pregnancy could be a predictor of preeclampsia.